Interconversion of Type C and D Strains of Clostridium botulinum by Specific Bacteriophages - Eklund, M. W. (1974)
These studies show that Clostridium botulinum types C and D cultures can be cured of their prophages and converted to either type C or D depending on the specific phage used. Strains of types C and D were cured of their prophages and simultaneously ceased to produce their dominant toxins designated as C(1) and D, respectively. Cured nontoxigenic cultures derived from type C strain 162 were sensitive to the phages from the toxigenic type C strain 162 and type D strain South African. When cured nontoxigenic cultures derived from strain 162 were infected with the tox(+) phages from the 162 strain of type C and the South African strain of type D, they then produced toxin neutralized by types C and D antisera, respectively. Cured nontoxigenic cultures isolated from the type D South African strain were only sensitive to the parent phage, and, when reinfected with the tox(+) phage, they produced toxin neutralized by type D antiserum. Type C strain 153 and type D strain 1873, when cured of their respective prophages, also ceased to produce toxins C(1) and D, but, unlike strain 162 and the South African strain, they continued to produce a toxin designated as C(2). When the cured cultures from strains 153 and 1873 were infected with the tox(+) phage from type D strain 1873, the cultures simultaneously produced toxin that was neutralized by type D antiserum. When these cured cultures were infected with the tox(+) phage from type C strain 153, the cultures produced toxin that was neutralized by type C antiserum. These studies with the four strains of C. botulinum confirm that the toxigenicity of types C and D strains requires the continued participation of tox(+) phages. Evidence is presented that types C and D cultures may arise from a common nontoxigenic strain.